Thomas Hardy's The return of the native - Hardy Thomas; Bloom, Harold (New York : everyman's library, 1992)
A collection of eight critical essays on Hardy's novel "The Return of the Native" arranged in chronological order of publication.
Includes index.
Bibliography: p. 143-146.
Keywords: Hardy, Thomas, -- 1840-1928.; Hardy, Thomas, -- 1840-1928.; English literature -- History and criticism